Durability improvement of cement stabilized pavement base using natural rubber latex. (May 2021) - Buritatum, Apinun; Horpibulsuk, Suksun; Udomchai, Artit; Suddeepong, Apichat; Takaikaew, Thaworn; Vichitcholchai, Nopparat; Horpibulsuk, Jitwadee; Arulrajah, Arul
Abstract: Cement stabilized soil as pavement base and sub-base materials has been extensively applied in various countries. Nevertheless, cement stabilized soil in tropical countries undergoes cracking problems and premature pavement distress, due to cyclic wet and dry seasons. Natural rubber latex (NRL) can be used as an additive to improve the serviceability and durability of cement stabilized soil. The effect of influence factors including soil type (low and high fines content), NRL type (low to high dry rubber content), NRL replacement ratio and cement content on the compressive strength prior to wetting and drying test (UCS0 ), cyclic wetting and drying compressive strength (UCS(w-d) ) and weight loss was examined in this study. The cement-NRL stabilized samples had higher UCS values than the cement stabilized samples, for all cement contents and NRL replacement ratios tested. The NRL films enhanced the cohesion (inter-particle forces) but retarded the hydration effects. The highest UCS value was found at an optimum NRL replacement ratio, which was 20%, 15%, and 10% for 3%, 5%, and 7% cement, respectively. The lowest weight loss and highest UCS(w-d) were also found at the optimum NRL replacement ratio. The UCS(w-d) of cement-NRL stabilized sample was found to be higher than that of cement stabilized samples at all w-d cycles, even for the same UCS0 . The equation of predicting UCS(w-d) at various w-d cycles was proposed for various influence factors based on the critical analysis of test results. The input of cement can be reduced by NRL replacement to attain the same target UCS0 and UCS(w-d), hence the reduction in carbon footprint. For the same UCS0  = 4.4 MPa, the carbon footprint of 4.4% cement stabilized soil was reduced to 30.7% as compared to the 3% cement and 20% NRL stabilized soil.